The Relationship between Perceived Benefits of Pre-practice Preparation and Clinical Practice in Normal Labour Care of Nursing Students - ชวเจริญพันธ์, วนิดา; สารถวัลย์แพศย์, นิชดา (Journal of The Royal Thai Army Nurses, 2019)
This cross-sectional survey study aimed to assess the relationship between the perceived benefits of pre practice preparation and self-assessment in normal labour care practices of nursing students. Fourth year nursing students-2016 academic year-of two nursing colleges, located in Bangkok and vicinity areas, under jurisdiction of Praboromarajanok Institute were recruited into the study. The total number of the samples was 192. Self-administered questionnaire consisting of personal information, perceived benefits of pre-practice preparation, and normal labour care practice self-assessment was used for data collection. The instrument was validated by three relavant experts and field-tested for reliability which yielded Chronbach’s alpha of 0.92, 0.97. Descriptive statistics and Pearson’s correlation were used for data analysis. Results showed that the samples perceived the benefits of the pre-practice preparation at good level and rated most of their labour care practices as good. It was found that the perceived benefits of pre-practice preparation were moderately and positively related to self-assessment labour care practices. Results of this study can be used to guide the improvement of the pre-practice preparation program to enhance analytical thinking and skills among the students to reinforce their confidence in providing effective labour care in the clinic.